Use of Image Storybook Media in Improving Speaking Skills in Group a Children in PAUD Al-Fajar Bengle, Talang District, Tegal Regency - Ainun Naharo, Hamidah; Myladiani, Keysa; Maheasy; Rakhmawati, Rani; Bilah, Sausana; Nisa, Sofatun; Hamid Samiaji, Mukhamad (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Improving the ability to speak in children is very important so that children can adapt and socialize with their peers. This study aims to improve the ability to speak through the medium of illustrated stories in group A children at PAUD Al-Fajar Bengle Talang Tegal Semester 1 of the 2022/2023 Academic Year. This research uses a descriptive-qualitative approach with a case study method. The subjects of this study were students at PAUD Al-Fajar Bengle Talang, totaling 13 children consisting of 7 boys and 6 girls. The learning action plan goes through 2 cycles, namely cycle I and cycle II. The results showed that the ability to speak through play activities with illustrated storybook media in the first cycle there were 7 children or 55% who were considered capable. Meanwhile, in cycle II there were 10 children or 65%. The essence of group children's activities at Paud A-lFajar Bengle Talang Tegal through the medium of picture storybooks is to improve speaking skills